2013
DOI: 10.1158/1078-0432.ccr-12-2880
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation as an Adjunct to Histopathology to Detect Prevalent, Inconspicuous Dysplasia and Early-Stage Neoplasia in Barrett's Esophagus

Abstract: Purpose: Endoscopic surveillance of Barrett's esophagus is problematic because dysplasia/early-stage neoplasia is frequently invisible and likely to be missed because of sampling bias. Molecular abnormalities may be more diffuse than dysplasia. The aim was therefore to test whether DNA methylation, especially on imprinted and X-chromosome genes, is able to detect dysplasia/early-stage neoplasia.Experimental design: 27K methylation arrays were used to find genes best able to differentiate between 22 Barrett's e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 48 publications
3
40
0
Order By: Relevance
“…51,52 Cytogenetic abnormalities detected by means of fluorescence in situ hybridization (FISH) and biomarker panels that identify multiple abnormalities in DNA content, gene expression, and DNA methylation have shown promise as predictors of cancer risk, as have some risk-stratification models that incorporate a variety of clinical, histologic, and molecular features. [52][53][54][55][56] However, none of these methods have yet been validated sufficiently to justify routine application in clinical practice.…”
Section: Epidemiol Ogymentioning
confidence: 99%
“…51,52 Cytogenetic abnormalities detected by means of fluorescence in situ hybridization (FISH) and biomarker panels that identify multiple abnormalities in DNA content, gene expression, and DNA methylation have shown promise as predictors of cancer risk, as have some risk-stratification models that incorporate a variety of clinical, histologic, and molecular features. [52][53][54][55][56] However, none of these methods have yet been validated sufficiently to justify routine application in clinical practice.…”
Section: Epidemiol Ogymentioning
confidence: 99%
“…They also found numerous previously undescribed hypermethylated genes in BE and EAC tissues, including genes encoding ADAM (A Disintegrin And Metalloproteinase) peptidase proteins, cadherins and protocadherins, and potassium voltage-gated channels. Alvi et al also used the HumanMethylation27 BeadChips to compare methylation patterns, focusing on imprinted and X chromosome genes, from 24 BE and 22 EAC samples (55) and validated their findings in retrospective and prospective cohorts to assess the ability of methylated genes to classify individuals as having prevalent BE, dysplastic BE, or EAC. They found four genes ( SLC22A18, PIGR, GJA12 , and RIN2 ) had the greatest area under curve (AUC=0.988) to distinguish between BE and dysplasia/EAC in their retrospective cohort.…”
Section: Epigenetic Alterations In Barrett’s Esophagus Barrett’mentioning
confidence: 99%
“…2527 For each of these studies, the selection of the biomarkers was based on the biology underlying cancer development, as determined by basic and translational research studies. A few of the more promising predictive biomarkers for cancer progression in Barrett’s esophagus have been validated in large studies; most with retrospective validation, while some studies include both a retrospective validation followed by prospective evaluation in a cohort of patients.…”
Section: Use Of Biomarker Panels To Assess Cancer Risk In Barrett’s Ementioning
confidence: 99%
“…25 Genes with differential methylation were identified and applied to cohort of samples including 60 non-dysplastic Barrett’s esophagus, 9 esophageal adenocarcinomas, and 28 dysplastic Barrett’s esophagus. From this retrospective validation, the investigators identified a 4-gene panel that was able to discriminate between non-dysplastic Barrett’s esophagus and Barrett’s-associated neoplasia with a high area-under-the-curve (AUC) of 0.988.…”
Section: Use Of Biomarker Panels To Assess Cancer Risk In Barrett’s Ementioning
confidence: 99%